Protective effects of erythropoietin against cuprizone-induced oxidative stress and demyelination in the mouse corpus callosum - Kashani, Iraj Ragerdi (Iran J Basic Med Sci, 2017)
OBJECTIVE(S): Increasing evidence in both experimental and clinical studies suggests that oxidative stress plays a major role in the pathogenesis of multiple sclerosis. The aim of the present work is to investigate the protective effects of erythropoietin against cuprizone-induced oxidative stress. MATERIALS AND METHODS: Adult male C57BL/6J mice were fed a chow containing 0.2 % cuprizone for 6 weeks. After 3 weeks, mice were simultaneously treated with erythropoietin (5,000 IU/kg body weight) by daily intraperitoneal injections. RESULTS: Our results showed that cuprizone induced oxidative stress accompanied with down-regulation of subunits of the respiratory chain complex and demyelination of corpus callosum. Erythropoietin antagonized these effects. Biochemical analysis showed that oxidative stress induced by cuprizone was regulated by erythropoietin. Similarly, erythropoietin induced the expression of subunits of the respiratory chain complex over normal control values reflecting a mechanism to compensate cuprizone-mediated down-regulation of these genes. CONCLUSION: The data implicate that erythropoietin abolishes destructive cuprizone effects in the corpus callosum by decreasing oxidative stress and restoring mitochondrial respiratory enzyme activity.